42 UMPSA graduands receive CBTM Diploma - Sakinah, Abdullah (UMPSA, 2023)
GAMBANG, 24 October 2023 - A total of 42 graduands of the collaboration programme between Universiti Malaysia Pahang Al-Sultan (UMPSA) and the Higher Education Leadership Academy (AKEPT) under the Lifelong Learning (PSH) agenda received their diplomas presented by the UMPSA Vice-Chancellor, Professor Dato’ Ts. Dr. Yuserrie Zainuddin at the recent UMPSA 18th Convocation Ceremony.